Svenja Kranich. 2016. Contrastive pragmatics and translation: Evaluation, epistemic modality and communicative styles in English and German. Amsterdam, Philadelphia: John Benjamins. P.p xiv + 204. ISBN 978 90 272 5666 9. - Ruskan, Anna (Kalbotyra, 2017)
...